Birth prevalence and determinants of neural tube defects among newborns in Ethiopia: A systematic review and meta-analysis - Beminet Moges Gebremariam; Dejene Hailu; Barbara J. Stoecker; Afework Mulugeta (PLoS ONE, 2025)
Background Neural tube defects (NTDs) are complex multifactorial disorders in the neurulation of the brain and spinal cord that develop in humans between 21 and 28 days of conception. Neonates with NTDs may experience morbidity and mortality, with severe social and economic consequences. Therefore, the aim of this systematic review and meta-analysis is to assess the pooled prevalence and determinants for neural tube defects among newborns in Ethiopia. Methods The protocol of this study was registered in the International Prospective Register of Systematic Reviews (PROSPERO Number: CRD42023407095). We systematically searched the databases PubMed, Science Direct, Cochrane Library, Google Scholar and Research Gate. Grey literature was searched on Google. Heterogeneity among studies was assessed using the I2 test statistic and the Cochran Q test statistic. A random effects model was used to estimate the birth prevalence of neural tube defects. Result Twenty-five articles were included in the meta-analysis to estimate the prevalence and determinants of neural tube defects in Ethiopia. A total of 611,354 newborns were included in the analysis. The pooled birth prevalence of neural tube defects was 83.40 (95% CI: 60.78, 106.02) per 10,000 births. The highest and lowest prevalence rates were 130.9 (95% CI: 113.52, 148.29) in Tigray and 28.60 (95% CI: 18.70, 38.50) per 10,000 births in Amhara regional states. Women’s intake of folic acid supplements and planned pregnancy were identified as protective factors for NTDs, while stillbirth history, use of any drugs during pregnancy, exposure to radiation, and pesticides during pregnancy were risk factors for neural tube defects. Conclusion The pooled birth prevalence of neural tube defects in Ethiopia was found to be high. Effective prevention interventions, especially focusing on periconceptional folic acid supplementation as well as folate fortification, should be prioritized alongside nutrition education, maternal health care, and environmental safety measures.